Respuesta comparativa del melón cucumis melo l. a la aplicación de fertilizantes orgánicos y mineral - Gamboa Gomez, Luis Alberto (2008)
The present research about comparative answer of melon (Cucumis melo L.) to the application of organic and minerals fertilizes was held at experimental farm sta. Ines wich is U.T.M property, it`s located 4.5 km in Machala – pasaje highway. The issues were: 1. What kind of reaction had the melon on organic fertilizes. 2. To find how much money I earn after the treatments of melons. Organic fertilizes used on melons: Algaenzins, green fish, Mixsapf biol and absolutly witness; all of them were used- In an interval of 12 days. The dossis of the first fertilize was 0,25 l ; the second one was 1,50 l ; the third one 0,50 l ; biol 2,50 l ; per treatment through foliage way. All of those fertilizes were compared with complefor wich was on 2,00 kg per treatment. Using this products in arranged blocks of land 4 times; wich means 24 experimental unites. To compare the results we used the Duncan test on 0,05 ; topics analized were: germination days, blossom days, weigh, length and diameter of fruits, number of fruit and of the harvest. Complefor had the best result on its kind, wich was as important as organic fertilizes. Among organic fertilizes was no problem, but the absolutely witness had a lower harvest of fruits per kg/ha, now we are aware organic fertilize.